In silico food allergenic risk evaluation of proteins extracted from macroalgae Ulva sp. with pulsed electric fields. (15th March 2019) - Polikovsky, Mark; Fernand, Francois; Sack, Martin; Frey, Wolfgang; Müller, Georg; Golberg, Alexander
Highlights: Method for selective allergens extraction with pulsed electric fields. Protein extraction with the pulsed electric field from Ulva sp. was optimized. Allergy assessment of proteins extracted from the seaweed Ulva sp. Proteomic analysis of Ulva sp. Abstract: Extraction of protein from macroalgae, currently defined as "novel food", is challenging and limited information about the health impacts of these proteins is available. Here, we report on a non-thermal, chemical-free green macroalgae Ulva sp. protein extraction by osmotic shock combined with pulsed electric fields (PEF) followed by hydraulic pressure. The extracted proteins were identified and annotated to allergens using sequence similarity. The allergenicity potential of PEF extracted proteins was compared to osmotic shock extracts and complete Ulva sp. proteome, extracted with the thermochemical method. The PEF extracts contained 'superoxide dismutase' (SOD), a known food allergen, osmotic shock extract contained 'troponin C', and thermochemical extract contained two additional potential food allergens 'aldolase A' and 'thioredoxin h'. This study shows an importance and the need for deep investigation of algal proteins and protein extraction technology health impacts prior to large-scale release to the market of "novel food" derived proteins.